Interferon-gamma release assays for diagnosis of latent TB infection in chronic kidney diseases and dialysis patients - Hayuk, Pattorn; Boongird, Sarinya; Pornsuriyasak, Prapaporn; Bruminhent, Jackrapong (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Patients with chronic kidney disease (CKD), especially end-stage kidney disease (ESKD), are at risk of developing tuberculosis (TB). The prevalence and predictors of LTBI assessed by a high-sensitivity, high-specificity test such as an interferon-gamma release assay (IGRA) has not been thoroughly explored. Methods All patients with CKD were prospectively recruited from September 2020 to November 2021 and retrospectively reviewed from December 2020 to November 2021. The prevalence of LTBI was determined using IGRA by CKD stage and dialysis type. Predictors of LTBI were assessed by logistic regression analysis. Results In total, 199 patients with CKD were enrolled (102 prospectively, 97 retrospectively). Of these, 173 patients were evaluable (mean age, 53 ± 16 years; 44% male). Ninety-five (55%) patients had ESKD and were maintained on renal replacement therapy. Overall, 39 (22.5%) patients had LTBI with a prevalence of 25.0%, 12.5%, 25.0%, 25.0%, and 24.2% among patients with CKD stage 1, 2, 3a, 3b, and ESKD, respectively (p=0.89). Among patients with ESKD, the prevalence of LTBI was higher in those on hemodialysis than in those on peritoneal dialysis (28.9% vs. 5.3%, p=0.03). In the multivariable analysis of patients with ESKD, drinking alcohol was significantly associated with LTBI (odds ratio, 8.51; 95% confidence interval, 1.24–58.38; p=0.029), and hemodialysis was marginally associated with LTBI (odds ratio, 8.14; 95% confidence interval, 0.95–69.91; p=0.056). Conclusion In TB-endemic settings, 20% of patients with CKD and 25% of patients with ESKD may have LTBI. Alcohol consumption and hemodialysis can help to identify high-risk patients with ESKD and potentially screen for LBTI.